1999
DOI: 10.1086/302539
|View full text |Cite
|
Sign up to set email alerts
|

A Second Gene for Autosomal Dominant Möbius Syndrome Is Localized to Chromosome 10q, in a Dutch Family

Abstract: Möbius syndrome (MIM 157900) consists of a congenital paresis or paralysis of the VIIth (facial) cranial nerve, frequently accompanied by dysfunction of other cranial nerves. The abducens nerve is typically affected, and often, also, the hypoglossal nerve. In addition, orofacial and limb malformations, defects of the musculoskeletal system, and mental retardation are seen in patients with Möbius syndrome. Most cases are sporadic, but familial recurrence can occur. Different modes of inheritance are suggested b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 21 publications
(23 reference statements)
0
52
0
1
Order By: Relevance
“…It will therefore be interesting to determine if any of these genes are linked to the disease locus. Transient ischemia during hindbrain development may also contribute to Moebius syndrome (e.g., Verzijl et al 1999). As VEGF-A gene expression is regulated by hypoxia, defective VEGF signaling might contribute to the aetiology of sporadic Moebius cases by simultaneously disturbing hindbrain vascularisation and facial nerve development.…”
Section: Potential Roles For Vegf/nrp1 Signaling In Neuronal Diseasesmentioning
confidence: 99%
“…It will therefore be interesting to determine if any of these genes are linked to the disease locus. Transient ischemia during hindbrain development may also contribute to Moebius syndrome (e.g., Verzijl et al 1999). As VEGF-A gene expression is regulated by hypoxia, defective VEGF signaling might contribute to the aetiology of sporadic Moebius cases by simultaneously disturbing hindbrain vascularisation and facial nerve development.…”
Section: Potential Roles For Vegf/nrp1 Signaling In Neuronal Diseasesmentioning
confidence: 99%
“…Linkage analysis in these two families identified two different loci cosegregating with the disorder, chromosome 3q21 -22 in HCFP1 and chromosome 10q21 -22 in HCFP2, 12,15 indicating genetic heterogeneity for this disorder.…”
Section: Discussionmentioning
confidence: 94%
“…Linkage analysis identified a locus on chromosome 10q21.3 -q22.1 cosegregating with the disorder. 15 Mutation analysis on the candidate genes EGR2, CTNNA3, and LRRTM3 located within or nearby the critical region failed to identify the underlying genetic defect for HCFP2 (B van der Zwaag, unpublished data). 20 For the smaller HCFP families, linkage analysis was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…68 Tischfield et al 46 reported horizontal gaze palsy and facial weakness in consanguineous patients with recessive HOXA1 mutations. However, in another pedigree study by Dumars et al 69 no mutations were detected in the genes PHOX2A, HOXA1, and KIF21A.…”
Section: Mö Bius Syndromementioning
confidence: 99%